Edge of tomorrow [videorecording (DVD)] - Cruise, Tom, 1962-; Gleeson, Brendan; Paxton, Bill; Blunt, Emily ([Publisher not identified], 2014)
In a near future, an alien race has hit the Earth in an unbeatable assault. Major William Cage has never seen a day of combat, but is dropped into a suicide mission and killed within minutes. Cage now finds himself thrown into a time loop-forcing him to live out the same day over and over, fighting and dying each time. With each "life", Cage learns more fighting skills, so that when he and warrior Rita Vrataski take the fight to the aliens, they are one step closer to defeating the enemy.